Implementation of Bamboo Chips from Pantai Labu Region in Enhancing Compressive Strength of Fiber Concrete - Wulan Dary, Rhini; Muhammad Ari Subhan Harahap; Mizanuddin Sitompul; Ernie Shinta Yosephine Sitanggang; Josep Hadipramana (LPPM Politeknik Aceh Selatan, 2024)
Concrete is widely used in construction due to its high compressive strength and durability. This study investigates the use of bamboo chips from the Pantai Labu region as a fiber material mixed with concrete to enhance its compressive strength. The research evaluates the effectiveness of different percentages of bamboo fiber chips, ranging from 0% to 2.5% by cement weight. Cylindrical concrete samples with diameters of 15 cm and heights of 30 cm were tested at 7, 14, and 28 days. The results demonstrate that adding 1% bamboo chips increased the compressive strength to 31.51 MPa, compared to the normal concrete strength of 30.04 MPa. This shows the potential of bamboo chips to improve the quality and sustainability of concrete production.